HOW CHILDREN PERCEIVE FOOD ADVERTISEMENTS ON TV: A SEMIOTICS ANALYSIS - Ma’rifah, Ulfatul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2020)
In digital era, advertising can reach people wider than before. Children are one of targeted consumers for food advertisements. Everyday children are shown by food advertisements while they are watching TV. These advertisements functioned both to deliver and utilize a wide variety of meaning, symbols and message called semiotics. Moreover, children are treated with variety of signs and symbols, but they have different ways of interpreting them.. This study investigated ten children (8-to-10 years old) to know about their perception towards food advertisements. Using semiotics analysis researcher interviewed children about ten food advertisements that are broadcasted on TV. The result shows that most of children can perceive well all signs and symbols communication conveyed by food advertisement. The most influence symbol that affected children to try product is food image that are usually performed in zoom mode and slow motion. Children also get understanding message, culture and value conveyed by food advertisements in positive side. It can support children to behave positively. While brand personal get les attention that brand character of food advertisements which children prefer more cartoon character as a brand mascot of food product.